(untitled) (Nepal Medical College Journal, 2025)
For selected end stage organ diseases, organ transplantation can be beneficial. Organ donation is a crucial procedure but the donors are not readily available. Different organs and tissues like kidney, liver, heart, blood, bone marrow, pancreas, intestines, etc. can be donated which can prolong the survival of patients in need and also improve their quality of life. The aim of the study was to assess the knowledge and attitude of organ donation among general population. A cross sectional analytical study was conducted with non – probability convenient sampling technique among 194 adults of three districts of Kathmandu Valley. Data collection was done online through google form shared via social media and emails. Data analysis was done using SPSS 16. Descriptive statistics like frequency, percentage, mean, standard deviation and inferential statistics like simple binary logistic regression and correlation were used for data analysis. More than one half (60.8%) of the respondents were of age ≤ 30 years. Majority (80.02%) belonged to middle class family according to Kuppuswamy socio-economic status tool. Majority (81.4%) of the respondents had poor knowledge whereas most (93.3%) had neutral attitude regarding organ donation. There was a significant negative correlation between knowledge and attitude regarding organ donation (p= <0.0001) at the significance level 0.05. This study has identified a need for awareness campaigns among general population regarding organ donation.